2019
DOI: 10.1186/s13148-019-0742-x
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing of MEIS2 in prostate cancer recurrence

Abstract: Background: Current diagnostic and prognostic tools for prostate cancer (PC) are suboptimal, resulting in overdiagnosis and overtreatment of clinically insignificant tumors. Thus, to improve the management of PC, novel biomarkers are urgently needed. Results: In this study, we integrated genome-wide methylome (Illumina 450K DNA methylation array (450K)) and RNA sequencing (RNAseq) data performed in a discovery set of 27 PC and 15 adjacent normal (AN) prostate tissue samples to identify candidate driver genes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…We originally demonstrated that increased mRNA expression of MEIS1 and MEIS2 in PrCa is correlated with significantly longer overall survival in a large cohort of watchful waiting patients with mid-range Gleason scores ( Chen et al, 2012 ). More recently, we and others demonstrated that patients harboring MEIS-positive tumors have a significantly favorable outcome; there is a step-wise decrease in both MEIS1 and MEIS2 expression as tumors progress to metastatic ( Bhanvadia et al, 2018 ; Jeong et al, 2017 ; Nørgaard et al, 2019 ). These correlative findings provide support to a tumor-suppressive role for MEIS1 and MEIS2 in PrCa.…”
Section: Introductionmentioning
confidence: 86%
“…We originally demonstrated that increased mRNA expression of MEIS1 and MEIS2 in PrCa is correlated with significantly longer overall survival in a large cohort of watchful waiting patients with mid-range Gleason scores ( Chen et al, 2012 ). More recently, we and others demonstrated that patients harboring MEIS-positive tumors have a significantly favorable outcome; there is a step-wise decrease in both MEIS1 and MEIS2 expression as tumors progress to metastatic ( Bhanvadia et al, 2018 ; Jeong et al, 2017 ; Nørgaard et al, 2019 ). These correlative findings provide support to a tumor-suppressive role for MEIS1 and MEIS2 in PrCa.…”
Section: Introductionmentioning
confidence: 86%
“…We refer readers to the original studies for the full lists of methylation markers. We focus on those studies that used measures of disease risk to identify potential biomarkers (for example, comparing methylation of patients of different GS, or different survival outcomes), rather than studies that compared methylation differences between benign and tumour tissue to identify disease-specific biomarkers, with assessment of their prognostic value as only a secondary step [ 113 , 114 , 115 , 116 , 117 , 118 , 119 ].…”
Section: Current State Of Prognostic Methylated Biomarkersmentioning
confidence: 99%
“…In this section, we summarise genome-wide prognostic methylation biomarker discovery studies in primary PCa tumours ( Table 2). We focus on those studies that used measures of disease risk to identify potential biomarkers (for example, comparing methylation of patients of different GS, or different survival outcomes), rather than studies that compared methylation differences between benign and tumour tissue to identify diseasespecific biomarkers, with assessment of their prognostic value as only a secondary step (for example, [113][114][115][116][117][118][119]). Low GS vs High GS: Cohort 1 -U: • No recurrence -6.5 ± 1.6…”
Section: Genome-wide Prognostic Biomarker Discovery Studiesmentioning
confidence: 99%